The Determinants of Executive Compensation in Family-Controlled Public Corporations - Gómez‐Mejía, Luis R.; Larraza‐Kintana, Martín; Makri, Marianna (Academy of Management Journal, 2003)
Little previous research has focused on the CEO's salary in family-controlled public firms. This lack is addressed by comparing and contrasting the executive compensation contracts of family-member CEOs and non-family CEOs. Data gathered during the years 1995 through 1998 from 253 randomly selected family-controlled public firms was analyzed. Professional managers with no family ties to firm owners were found to be compensated at a higher rate than executives with family ties. This relative pay disadvantage increases as the family ownership position improves (which depresses the pay of the family CEO) and R&D investments increase (which improve the pay of the professional CEO but not the family CEO). On the other hand, family ties protect a CEO from bearing excessive personal risk, as indicated by a greater compensation premium, as uncontrollable (systematic) business risk increases. These findings point to a complex company dynamic: when family-member CEOs are in charge, altruistic motives exist that often result in risk protection for the CEO's personal income rather than in higher pay for these executives. (SFL)